Effectiveness of the cataract educational and behavioral skills program for patients undergoing cataract surgery and primary caregivers, Pathum Thani Hospital - Pukkhaow, Lamitr; Gongsumrit, Pensri; Yonchoho, Nichapa; Kantapokai , Worrawan (Thai Journal of Nursing, 2024)
This quasi-experimental research aims to compare knowledge of cataracts and behavioral skills after receiving the cataract educational and behavioral skills program in patients undergoing cataract surgery and their primary caregivers, Pathum Thani Hospital. A sample of 60 patients undergoing cataract surgery and 60 primary caregivers was purposively selected. They were equally divided into the experimental group and the control group. Research instruments include the educational program on knowledge of cataract disease and behavioral skills. Data were collected using the questionnaires on cataract knowledge and behavioral skills. The index of item-objective congruence were between .93 - .97 while the Kuder-Richardson 20 reliability coefficient was .60 and the inter-rater reliability was 1.00. Descriptive statistics and independent t-test were used in data analysis. The results found that after using the program, the experiment groups, including both the patients and the primary caregivers, had significantly greater cataract knowledge and behavioral skills compared to the control groups at p < .05.